Calculation of surface settlement and pile foundation deformation caused by shield machine tunnelling along curve section - Zeng, Feng; Gao, Yang; Chen, Fujiang; He, Qingqing; He, Zhihao (Frontiers in Ecology and Evolution, 2022)
The shield machine tunnelling along the curve section causes more disturbance to the surrounding environment than the straight section. Pile foundation is the most commonly used foundation form in high-rise buildings, and high-rise buildings have extremely high requirements for controlling non-uniform deformation. Therefore, it is necessary to study the surface settlement and the deformation law of pile foundations caused by shield machine tunnelling along the curve section. Considering the shield machine tunnelling factors along the curve section and the coupling effect of piles and soil, the analytical calculation formula of the ground settlement and the pile foundation deformation caused by the shield machine tunnelling along the curve section is deduced. According to the actual project situation, a finite difference model (FDM) is constructed, and the correctness of the FDM and analytical prediction formula is verified by comparing the on-site monitoring data. The research shows that the error among the FDM results, the analytical prediction results, and the on-site monitoring data are small, and the surface settlement and pile foundation deformation meet the construction control standards. The friction resistance of the shield shell, the integrative gap at the shield tail (IGST), and the over-cutting gap (OG) are the main factors leading to the surface settlement. However, the shield shell friction and OG are the main reasons leading to the inner settlement of the curve section being more prominent than the outer side. The difference in the pile foundation settlement on both sides of the curve section is slight, the maximum settlement difference rate is 1.8%, and the maximum horizontal deformation rate of the pile foundation on the inner and outer sides is 9.2%, which shows that the horizontal deformation of the pile foundation is more sensitive to the asymmetrically distributed construction factors.